Alternative Scriptwriting Beyond the Hollywood formula - Dancyger, Ken.; Rush, Jeff. (Burlington, MA Abingdon, Oxon Focal Press, 2013)
This guide to alternative scriptwriting pushes you to challenge yourself and break free of tired, formulaic writing - bending and breaking the rules of storytelling as we know them.
includes index
Keywords: Motion picture authorship; Motion picture plays -- Technique